Management of Information and Communication Technology (ICT) Extracurricular Activities for Strengthening Digital Literacy among Students at an Islamic Elementary School - Amalia Fazrin; Moh. Bisri (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The management of technology-based extracurricular activities has become an increasingly important strategy for cultivating students' digital competencies in twenty-first-century education. This study examined the management of an Information and Communication Technology (ICT) extracurricular program at SDTQ Al Mujahidin Surakarta, an Islamic elementary school that combines Qur'anic-memorization (tahfidz) education with technology-based learning, during the 2025/2026 academic year. Specifically, the study analyzed (1) how the program was planned, organized, implemented, and evaluated; (2) the factors that supported and inhibited its implementation; and (3) the strategies used by the school to address these constraints. A qualitative case study design was employed. Data were obtained from the school principal, the curriculum vice-principal, the ICT extracurricular teacher, students, and parents through semi-structured interviews, non-participant observation, and documentation, and were validated through source and technique triangulation. Data were analyzed using the interactive model of Miles, Huberman, and Saldáña. The findings show that the program was managed through four interrelated functions, planning, organizing, implementation, and evaluation, structured around a weekly, practice-based curriculum covering basic computer operation, application use, simple graphic design, safe internet use, and introductory coding. Teacher and student accounts indicate that this practice-based approach was associated with improved confidence and basic computer competence, although the school's evaluation remained largely observational (attendance, enthusiasm, and informal assessment of practical tasks) rather than based on a validated digital literacy instrument. Implementation was supported by the principal's commitment, teacher competence, student enthusiasm, and laboratory facilities, but constrained by a limited number of computers, restricted instructional time under a full-day school schedule, heterogeneous student skill levels, and unstable internet connectivity. The school addressed these constraints through ability-based student grouping, rotational laboratory scheduling, and adaptive teaching strategies. These findings suggest that structured, function-based management, combined with deliberate attention to Islamic values, can support the cultivation of digital literacy in faith-based elementary education, while also indicating a need for more systematic, indicator-based evaluation tools in future practice.